2015
DOI: 10.1590/1984-70332015v15n2n20
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation changes in Cucurbitaceae inter-species grafting

Abstract: -Grafting has been used to improve yield, fruit quality and disease resistance in a range

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
1
31
0
7
Order By: Relevance
“…Recent evidence has suggested that modifications of DNA methylation may be central to explaining grafting‐induced variations (Avramidou et al ., ; Kasai et al ., ). In this study, whole genome bisulfite sequencing (WGBS) was conducted to investigate the variation in the DNA methylomes of r‐CCC4.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent evidence has suggested that modifications of DNA methylation may be central to explaining grafting‐induced variations (Avramidou et al ., ; Kasai et al ., ). In this study, whole genome bisulfite sequencing (WGBS) was conducted to investigate the variation in the DNA methylomes of r‐CCC4.…”
Section: Resultsmentioning
confidence: 98%
“…The purposes of grafting are varied, but the most common use is the clonal vegetative propagation of heterogenic trees that harbour desirable traits (Tsutsui and Notaguchi, ). Grafting‐induced changes in phenotype and genotype have been observed and confirmed in model plants and woody species (Frankel, ; Clearwater et al ., ; Stegemann and Bock, ; Avramidou et al ., ; Melnyk, ). For example, Taller et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its long history and practical utilities of plant vegetative grafting, the underlying mechanisms for graft-induced phenotypic and physiological changes remains to be fully understood. It is generally accepted that metabolic substances including those that may produce large biological effects, such as hormones, proteins and signal molecules, could be transferred from one grafting partner to the other 18 , 28 , 38 , 42 causing changes in graft partners. Also healing response is known to involve in salicylate 36 , 37 , jasmonate 38 , and other plant hormone signals 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Grafting approaches reported here could be used in cotton improvement studies. For instance, interspecific grafting experiments would allow the increase in some physiologic, agronomic, genetic and epigenetic traits 34 , 42 . Grafting experiments have been already used in cotton for different purposes.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are also exchanged between the scion and rootstock in grafted watermelon, which may regulate the growth and development of the scion (Cookson and Ollat, 2013; Liu et al, 2013). A genomic DNA methylation analysis was performed in cucumber and melon scions by a grafting system using cucurbitaceous inter-grafting (Avramidou et al, 2015). Recently, some research identified many DEGs involved in various metabolic processes in grafted cucumber and verified by qRT-PCR (Miao et al, 2019a; Miao et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%